Spotify library management & data retrieval with user-defined metadata - Michálek, Ondřej (2022)
Spotify offers broad range of music across many genres. It also allows users to build their own library of favourite music pieces, and categorise them in playlists. These playlists offer a single-criterion categorisation which is popular across many music streaming platforms, but might allow insufficient control over managing the whole library, as literature suggests. The literature suggests adding metadata tag to each song, enabling the user a better search using multi-criterion constraints instead of a linear search of a playlist. Initial research was divided in 3 distinct topics - Music digital library organisation, Querying the library, and Spotify ecosystem integration. Based on this step, the initial knowledge was obtained to design an application in PHP allowing users to add this metadata to songs in their Spotify library. This application was developed into a MVP using the Lean Startup method, where in 5 iterations was obtained a feedback from 10 participants. Based on this feedback, a conclusion was made that tagging music is a idea that half of the participants do not desire, and the other half mostly require a simplified concept. Rearranging contents of playlists directly in Spotify and a search that finds songs contained across multiple playlists. Due to these findings, a future progress was proposed for developing a different application containing adjusted features. This application should be built on a different stack, as PHP with a Symfony framework is unsuitable for this purpose.